2019
DOI: 10.34062/afs.v6i3.7617
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos da precipitação pluviométrica em um povoamento jovem de Eucalyptus dunnii no Bioma Pampa

Abstract: A interação de plantios florestais com a precipitação influi tanto no crescimento e desenvolvimento da floresta quanto na disponibilidade de água para percolação e abastecimento do lençol freático, e assim, a fase de desenvolvimento do povoamento é um aspecto relevante a ser observado. Objetivou-se avaliar a precipitação pluviométrica em Eucalyptus dunnii através do monitoramento de um povoamento durante o período de um ano, com início aos 16 meses de idade, no município de Alegrete-RS. A precipitação dentro d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…has shown high correlations between variables. In a stand of Eucalyptus dunni aged between 1.4 and 2.4 years, Corrêa et al (2019) found correlations between rainfall and throughfall, stemflow and canopy interception in the order of 0.99, 0.83 and 0.53%, respectively.…”
Section: Rainfall Partitioningmentioning
confidence: 91%
See 1 more Smart Citation
“…has shown high correlations between variables. In a stand of Eucalyptus dunni aged between 1.4 and 2.4 years, Corrêa et al (2019) found correlations between rainfall and throughfall, stemflow and canopy interception in the order of 0.99, 0.83 and 0.53%, respectively.…”
Section: Rainfall Partitioningmentioning
confidence: 91%
“…Supangat et al (2012) evaluating the behavior of rainwater after interaction with the canopy of six-year-old Eucalyptus pellita found an interception of 15.4%. Corrêa et al (2019) evaluating a stand of Eucalyptus dunnii in Alegrete, RS at 16.5 months of age observed that the precipitation was 1,586 mm, with 7% being intercepted by the canopy of the stand. The throughfall corresponded to 98% of the effective precipitation, the remaining 2% referring to stemflow.…”
Section: Rainfall Partitioningmentioning
confidence: 99%
“…According to Gay and Murphy (1985), approximately between 30 -70% of the dry deposition of SO4 2can be retained in the canopy. Corrêa et al (2019) evaluating an E. dunni stand 16.5 months old, found that due to the concentration of ions there was a greater contribution of elements after the interaction of precipitation with the forest canopy.…”
Section: Nutrients Totalmentioning
confidence: 99%